2015
DOI: 10.1016/j.jegh.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal cohort study of the relationship between Thimerosal-containing hepatitis B vaccination and specific delays in development in the United States: Assessment of attributable risk and lifetime care costs

Abstract: Epidemiological evidence suggests a link between mercury (Hg) exposure from Thimerosal-containing vaccines and specific delays in development. A hypothesis-testing longitudinal cohort study (n=49,835) using medical records in the Vaccine Safety Datalink (VSD) was undertaken to evaluate the relationship between exposure to Hg from Thimerosal-containing hepatitis B vaccines (T-HBVs) administered at specific intervals in the first 6months of life and specific delays in development [International Classification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Also, since a total of 3,911,498 weighted-persons with LDs were examined, and 1,025,695 weighted persons with LDs were attributable to increased blood Pb, this means that 26.2% of all LDs (or about 1 in 3.8 LDs) were associated with increased blood Pb levels. As a result, the majority of LDs are caused by other environmental and/or genetic factors [ 10 , 11 ]. This finding is plausible because there are other known toxicants that are associated with LDs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since a total of 3,911,498 weighted-persons with LDs were examined, and 1,025,695 weighted persons with LDs were attributable to increased blood Pb, this means that 26.2% of all LDs (or about 1 in 3.8 LDs) were associated with increased blood Pb levels. As a result, the majority of LDs are caused by other environmental and/or genetic factors [ 10 , 11 ]. This finding is plausible because there are other known toxicants that are associated with LDs.…”
Section: Discussionmentioning
confidence: 99%
“…The best epidemiology can do is to indicate the confidence limits to an observation occurring by chance. As discussed earlier, thiomersal exposure has been linked with the diagnosis of Autism, Hyperkinetic syndrome of childhood, Developmental delay and other Neurodevelopmental disorders in several studies [27][28][29][30][31]. Increased vulnerability to this preservative as a result of abnormality of chemical defence mechanisms has been reported in children with ASD [33].…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were found in another epidemiologic study which evaluated organic Hg exposure from Thiomersal in Haemophilus influenzae type b (Hib)-containing vaccines administered at specific times within the first 15 months of life and concluded a significantly increased risk of Pervasive development disorders in such children [29]. Increasing Hg exposure from thiomersal in Hepatitis B vaccine administered in first six months of life has been found to be associated with a higher risk of developing hyperkinetic syndrome of childhood as well as developmental delay [30,31].…”
Section: Studiesmentioning
confidence: 92%
“…Three of these studies used different statistical methods applied to the Vaccine Safety Datalink (VSD) to evaluate infant Thimerosal-containing hepatitis B vaccine exposure and its relation to outcomes that are common diagnoses among those receiving special education services, such as learning disabilities, autism, and emotional disturbances. For example, a 2016 longitudinal cohort study evaluated the relationship between exposure to Hg from Thimerosal-containing hepatitis B vaccines administered at specific intervals within the first six months of life and the long-term risk of being medically diagnosed with a learning disability [ 8 ]. These investigators observed that infants receiving additional doses of Hg from Thimerosal-containing hepatitis B vaccines administered within the first month, the first two months, and the first six months of life, in comparison to infants receiving no Hg doses from Thimerosal-containing hepatitis B vaccines, were at a significantly increased long-term risk of being diagnosed with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%